PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP NIAT BELI ULANG DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING (STUDI PADA PELANGGAN TEH RTD MEREK TEH GELAS DENGAN KEMASAN BOTOL DI INDOMARET KECAMATAN GUBENG) - AJI, IBRAHIM (Jurnal Ilmu Manajemen (JIM), 2018)
Abstract Increased competition among companies in the beverage industry, especially ready-to-drink tea in Indonesia, make the company must keep the product in order to satisfy consumers so that it can grow the repurchase intention by improving the quality of the product and provide an affordable price.The purpose of this research is to analyze and discuss the effect of product quality, and price on repurchase intention with satisfaction as an intervening variable. This research is conclusive research. The correspondent in this research is Teh Gelas customers who have bought and consumed Teh Gelas product more than twice and aged minimum 19 years. The sampling technique used judgmental sampling technique with a sample of 220 respondents. The research instrument used was questionnaire, and then the data obtained was processed by using path analysis with AMOS 22 program. The result of the research shows that product quality has significant influence to satisfaction, price variable has significant effect to satisfaction, variable of satisfaction has significant effect to repurchase intention, product quality variable has significant effect to repurchase intention, and price variable has significant effect to repurchase intention.. Keywords: product quality, price, satisfaction, re-purchase intention